A Retrospective study of analysis of reasons for discard of blood and blood components - Dr Mamatha SV; Dr Chaithra H; Dr Susmitha NS; Dr Rajatha Anand (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Blood transfusion is an essential element in modern health care. Transfusion of blood and blood components has become an integral part of patient management in modern medicine. Human blood till date has no substitute. Demand of blood and its components always outpace its supply.This emphasizes the need for proper utilization of blood and its components with preferably “NO” or minimal wastage. Materials and methods: A Retrospective study of analysis was carried out at Sri Siddhartha Medical College Hospital Blood bank from 1st January 2017 to December 31st 2017. Results: Out of 1806 whole blood bags, 371 (5.21%) were discarded. 137(36.9%) units were discarded because of transfusion transmitted infections (TTIs). Out of 11809 components prepared, 1027(8.6%) blood components blood were discarded. Most common component discarded was platelet (40.7%) and reason for discard was date of expiry due to non-utilization. Conclusion:Blood being irreplaceable source, discard rate can be reduced by proper counseling of blood donors and adhering to strict donor deferral criteria.Discard rate of platelet concentrate can be minimized by preparing platelet concentrate on request and also by using modern technique like Apheresis.